PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI WORD OF MOUTH SEBAGAI VARIABEL INTERVENING - Rizkiana, Citra; rieny, Sulistyorini; NSS, Rr Lulus Prapti; Triyani, Dian (ITB AAS Indonesia Surakarta, 2024)
This research examines the influence of Brand Image and Product Quality on Purchasing Decisions through Word of Mouth as an Intervening Variable (Case Study Grilled Chicken Arto Moro Pekalongan). The method used in this research is Partial Least Square (PLS) using SmartPLS version 3 software with a total of 91 research respondents. The research results show that Brand Image and Product Quality positively and significantly affect Purchasing Decisions and Word of Mouth. This research found that Word of Mouth positively and significantly affects Purchasing Decisions. Furthermore, this research examines the mediation of Word of Mouth in the relationship between Brand Image and Product Quality on Purchasing Decisions. The research results show that Word of Mouth can mediate the relationship between Brand Image and Product Quality on Purchasing Decisions.